السلطة الوطنية المستقلة للانتخابات ضمانة لنزاهة العملية الانتخابية )انتخاب رئيس الجمهورية 12/12/2019 أنموذجا - قرين عبد القادر, عبد القادر (جامعة الوادي.University eloued, 2021)
لقد ساير المشرع الجزائري ما تبناه الحراك الشعبي في الجزائر، و أنشأ السلطة الوطنية المستقلة للانتخابات بموجب القانون العضوي رقم: 19/07 المتعلق بالسلطة الوطنية المستقلة للانتخابات، و تعديل القانون العضوي رقم 16/10، المتعلق بنظام الانتخابات، بالقانون رقم 19/08، بغية ضمان شفافية و نزاهة و مصداقية العملية الانتخابية، و بالتالي ستؤدي إلى حماية حقوق و الحريات العامة للمواطنين، منح لها الشخصية المعنوية و الاستقلال الإداري و المالي، لذلك مكنها من آليات عضوية، تتضمن تشكيلة متنوعة من الكفاءات الوطنية و المتخصصين في مختلف المجالات، و استثنى منها الإدارة و الأحزاب السياسية، بغية ممارسة مهامها بكل حيادية وبعيدا عن الضغوط التي يمكن أن تسببها أي سلطة أو هيئة مركزية أو محلية، أيضا منح لها آليات وظيفية و مادية تتمثل في كل الصلاحيات المتعلقة بالمراحل التي تمر بها العملية الانتخابية من بدايتها إلى إعلان النتائج، و ركزنا في دراستنا على انتخاب رئيس الجمهورية 12/12/2019، باعتبارها أول تجسيد فعلي لدور السلطة الوطنية المستقلة للانتخابات.Elections are currently the only democratic way to assign power. It is not possible in any way to choose rulers except through this way, through which the people express their will in this choice. He is the owner of sovereignty. He exercises it through his representatives, in the executive and legislative authority, and in He contributes to the selection of his representatives in the exercise of public affairs at the national and local levels. The challenge in the modern era is no longer limited to just carrying out electoral operations, but rather to proceed with the necessity of achieving the real purpose of these operations, which is the true expression of the popular will in choosing rulers, without confiscation and without emptying the essence of exercising the right to vote and to run, guaranteed in various International charters and national constitutions, and this challenge can only be achieved through a set of principles, mainly related to the election cycle, and assigning the task of organizing it to an independent body located at the same distance from all political formations and institutions associated with the elections, in addition to establishing sufficient guarantees to monitor the various processes electoral.
قانون اداري
Keywords: السلطة الوطنية – السلطة المستقلة – العملية الانتخابات – الضمانات القانونية.: national authority - independent authority - process elections - legal guarantees.